2005
DOI: 10.1176/appi.ajp.162.12.2269
|View full text |Cite
|
Sign up to set email alerts
|

Is Impaired Set-Shifting an Endophenotype of Anorexia Nervosa?

Abstract: Both affected and unaffected sisters had more set-shifting difficulties than unrelated healthy women. This finding, together with the replicated finding that set-shifting difficulties persist after recovery, suggests that set-shifting difficulties are trait characteristics and may inform the search for the endophenotype in anorexia nervosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
242
2
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(271 citation statements)
references
References 31 publications
21
242
2
6
Order By: Relevance
“…94 Importantly, these set-shifting deficits persist after recovery from AN. 95 In addition, sisters of women with AN exhibit significantly impaired set shifting compared to controls, 12 comparable to that of their siblings with AN. Further appeal with respect to this measure of cognitive function as a potential endophenotype is its association with the dopaminergic system.…”
Section: Set-shiftingmentioning
confidence: 97%
See 1 more Smart Citation
“…94 Importantly, these set-shifting deficits persist after recovery from AN. 95 In addition, sisters of women with AN exhibit significantly impaired set shifting compared to controls, 12 comparable to that of their siblings with AN. Further appeal with respect to this measure of cognitive function as a potential endophenotype is its association with the dopaminergic system.…”
Section: Set-shiftingmentioning
confidence: 97%
“…Thus many fields of psychiatry have embraced research on endophenotypes, however, only four references were located in eating disorder field. [12][13][14][15] …”
Section: Can Endophenotypes Inform Diagnostic Criteria?mentioning
confidence: 99%
“…163 Paradigms measuring behaviours under specified circumstances may overcome the limitations of self-report questionnaires and prove to be valid measures of intermediate phenotypes. [164][165][166][167][168] For example, it has been demonstrated that 5-HTTLPR s allele carriers have more attentional bias towards anxiety-related stimuli compared to ll homozygotes in the dot-probe task. 168 A complementary approach will be the identification of biological endophenotypes.…”
Section: Genetic Control Of the Environmentmentioning
confidence: 99%
“…While some traits associated with ASD, such as emotional theory of mind, have been found to reduce in recovered AN groups (Oldershaw et al 2010), other traits including difficulties with set-shifting, or flexible thinking, appear to persist after weight gain (Tchanturia et al 2004;Gillberg et al 2010;Danner et al 2012;Lindner et al 2014). Recent reports suggest that set-shifting inefficiencies are present in children with AN who have had a relatively short duration of illness (Lang et al 2015a) and relatives with AN (Holliday et al 2005;Roberts et al 2010;Lang et al 2015b). Conversely, fasting in healthy controls (HCs) has been found to reduce set-shifting test performance, suggesting that starvation may exacerbate underlying difficulties in this domain (Bolton et al 2014;Pender et al 2014).…”
Section: Introductionmentioning
confidence: 99%